2007
DOI: 10.1016/j.ejcts.2007.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 and interleukin 1 receptor antagonist as early markers of complications after lung cancer surgery

Abstract: Elevated concentrations of IL-6 and IL-1ra in pleural fluid on postoperative day 1 are promising early markers of postoperative complications. Elevated concentrations of IL-6 and IL-1ra in serum are good early markers of severity of surgical injury and may reflect development of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
(15 reference statements)
1
12
2
4
Order By: Relevance
“…Применение продленной эпидуральной анал-гезии (ЭА) в послеоперационном периоде является фактором ограничения стрессовой реакции организ-ма на хирургическую травму и позитивно влияет на результаты хирургического лечения [8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Применение продленной эпидуральной анал-гезии (ЭА) в послеоперационном периоде является фактором ограничения стрессовой реакции организ-ма на хирургическую травму и позитивно влияет на результаты хирургического лечения [8].…”
Section: Introductionunclassified
“…Хирургическая травма стимулирует выработ-ку цитокинов в раннем послеоперационном периоде, приводя к развитию синдрома системного воспали-тельного ответа (ССВО) а иногда и синдрома полиор-ганной недостаточности (СПОН) [8]. Эти изменения могут контролироваться путем измерения активно-сти или концентрации иммунокомпетентных клеток (медиаторов воспаления) в сыворотке [10].…”
Section: Introductionunclassified
“…For instance, Szczesny et al have recently shown that following surgeries such as lung surgeries, serum as well as pleural elevation of the IL-1ra level is a strong indicator of postoperative complications [7]. Similarly, Slotwinski et al have recently shown that following procedures such as pancreaticoduodenectomy, IL-1ra appears to be one of the most sensitive and important markers to detect early antiinflammatory response to enteral immunonutrition [8].…”
mentioning
confidence: 98%
“…Meanwhile the concomitant sequelae, including postoperative pain, functional limitation, and potential risk of infection, may lower the quality of surgery. Furthermore, some studies (3)(4)(5) have investigated the role of immune complexes, lymphocytes and cytokines existing in the pleural fluid, implicating a potential immune impairment after losing significant pleural fluid in a short time after surgery.…”
Section: Original Articlementioning
confidence: 99%